Two-Year Follow Up of the LATERAL Clinical Trial: A Focus on Adverse Events. (19th April 2021) - Wieselthaler, Georg M.; Klein, Liviu; Cheung, Anson W.; Danter, Matthew R.; Strueber, Martin; Mahr, Claudius; Mokadam, Nahush A.; Maltais, Simon; McGee, Edwin C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The LATERAL trial validated the safety and efficacy of the thoracotomy approach for implantation of the HeartWare HVAD System, leading to Food and Drug Administration approval. We sought to analyze 24-month adverse event (AE) rates, including a temporal analysis of the risk profile, associated with the thoracotomy approach for the HVAD system. Methods: AEs from the LATERAL trial were evaluated over 2 years postimplant. Data was obtained from the Interagency Registry for Mechanically Assisted Circulatory Support database for 144 enrolled United States and Canadian patients. Temporal AE profiles were expressed as events per patient year. Results: During 162.5 patient years of support, there were 25 driveline infections (0.15 events per patient year), 50 gastrointestinal bleeds (0.31 events per patient year), and 21 strokes (0.13 events per patient year). Longitudinal AE analysis at follow-up intervals of <30 and 30 to 180 days, and 6 to 12 and 12 to 24 months revealed the highest AE rate at <30 days, with a decrease in total AEs within the first 6 months. After 6 months, most AE rates either stabilized or decreased through 2 years, including a 95% overall freedom from disabling stroke. Conclusions: Two-year follow-up of the LATERAL trial revealed a favorable morbidity profile in patients supported with the HVAD system, as AE rates were more likely to occur in the first 30 days postimplant, and overall AE rates were significantly reduced after 6 months. Importantly, 2-year freedom from disabling stroke was 95%. These data further support the improving AE profile of patients on long-term HVAD support. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT02268942.